2005
DOI: 10.1021/ol051575+
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-Triggered Complete Chemo-Switch:  From Efficient Aldehyde−Alkyne−Amine Coupling to Efficient Aldehyde−Alkyne Coupling in Water

Abstract: [reaction: see text] A phosphine ligand served as a remarkable chemo-switch for the silver-catalyzed reaction of alkynes with aldehydes in the presence of amines in water. Exclusive aldehyde-alkyne-amine coupling product was observed in the absence of phosphine, whereas in the presence of a phosphine ligand, exclusive aldehyde-alkyne coupling product was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 131 publications
(51 citation statements)
references
References 16 publications
1
50
0
Order By: Relevance
“…With Cu(I)-pybox as a chiral catalyst, a highly enantioselective alkyne-imine addition in either water or toluene also was reported by us (66,67). We also developed the coupling of alkynes with N-acylimines and N-acyliminium ions by using a CuBr catalyst, and the gold-or silver-catalyzed coupling reactions of alkyne, aldehyde, and amine in water (68)(69)(70)(71)(72)(73)(74)(75). Although these are effective methods, these methods need a leaving group or an imine formed from aldehyde and amine.…”
mentioning
confidence: 68%
“…With Cu(I)-pybox as a chiral catalyst, a highly enantioselective alkyne-imine addition in either water or toluene also was reported by us (66,67). We also developed the coupling of alkynes with N-acylimines and N-acyliminium ions by using a CuBr catalyst, and the gold-or silver-catalyzed coupling reactions of alkyne, aldehyde, and amine in water (68)(69)(70)(71)(72)(73)(74)(75). Although these are effective methods, these methods need a leaving group or an imine formed from aldehyde and amine.…”
mentioning
confidence: 68%
“…[81,82] Later, Li and co-workers found that silver complexes, such as Cy 3 PAgCl, were also a choice of catalyst for the addition of terminal alkynes to aldehydes. [83] Interestingly, the phosphine ligand served as a remarkable chemo-switch for the reaction of aldehydes with alkynes in the presence of amines in water. In the presence of a phosphine ligand, silver catalyzed exclusive aldehyde-alkyne coupling, whereas exclusive aldehyde-alkyne-amine (A 3 ) coupling occurred in the absence of phosphine [Eq.…”
Section: 3 Reaction With Carbonyl Compoundsmentioning
confidence: 99%
“…Recently, Sigman et al successfully developed a new, water-soluble cobalt catalyst, CpCo-h 4 -cyclooctadiene, to catalyze alkyne cyclotrimerization in water at an elevated temperature [Eq. (83)]. Protection of alkyne functional groups, such as amine, hydroxy, ketone, ester, and carboxylic acid, was not required in this aqueous [2 + 2 + 2] cyclotrimerization chemistry.…”
Section: A C H T U N G T R E N N U N G [2+2+2] Cyclotrimerizationmentioning
confidence: 99%
“…The catalyst showed much higher catalytic activities than the reported Ag (I)-phosphine complex, [5] and gave good to excellent yields for a variety of aldehydes and terminal alkynes. Furthermore, the catalyst could be recovered and reused effectively, no obvious reduction on catalytic activity was observed for several recycles.…”
mentioning
confidence: 84%
“…[5] Recently, much attention has been attracted to the use of nanoparticles as catalysts in organic reactions, [6] because their intriguing properties are different from those of their corresponding bulk materials. Metal nanoparticles have a characteristic high surface area that translates into more active sites per unit area, and can maximize the reaction rates and minimize consumption of the catalyst.…”
mentioning
confidence: 99%